Pelatihan cipta dan baca puisi bagi Siswa SMP di Kabupaten Gowa - Anshari Anshari; Aswati Aswati; Nurhusna Nurhusna (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Various problems are found among junior high school students in creative learning and reading poetry. One problem that will be solved is generally, junior high school students have not been able to create or write and read poetry well so that teaching and learning activities become less optimal. Students tend to be less creative in the use of diction in writing activities (copyright) and less able to read poetry. Based on observations and interviews from several teachers, generally most students seem to dislike learning to write (copyright) poetry and read poetry. This is because some students feel unable to write and read poetry. Most teachers think students are less creative in choosing words when writing poetry and lacking confidence when reading poetry. So that learning becomes less optimal. Students seem less creative, less interested, less active during the learning process. The student's imagination space is still confined and the student's inner sensitivity causes him to not succeed in finding the spirit of poetry. Through this PKM training, students are expected to have confidence in writing (copyright) and reading poetry, and students are more creative in choosing words in writing learning and more expressive when reading poetry. This PKM program aims to provide copyright training and read poetry to students of Bontonompo 2 Public Middle School in Gowa Regency. Thus, students of SMP Negeri 2 Bontonompo in Gowa Regency are able and skilled at creative activities and read poetry at school, especially in classroom learning activities. So that students are more motivated to follow the Indonesian language teaching and learning process. In general, the method used in this activity was in the form of training for students of Bontonompo Public Middle School 2 in Gowa Regency. Training activities begin with the provision of creative engineering material, read poetry. Then, followed by creative practices read poetry. Outcomes generated in science and technology transfer activities for the community through creative training activities and reading poetry for students of Gowa District 2 State Junior High School 2, including (1) Students of SMP Negeri 2 Bontonompo, Gowa Regency are able to write (copyright) and read poetry well; (2) Students of SMP Negeri 2 Bontonompo in Gowa Regency will be creative in applying some writing techniques (copyright) and reading poetry; and (3) Students of SMP Negeri 2 Bontonompo in Gowa Regency will encourage their friends to become peer tutors in writing and reading poetry.